Quinazolin derivatives as emerging alpha-glucosidase inhibitors - Ankireddy, Ashok Reddy; Gundla, Rambabu; Balaraju, Tuniki; Banothu, Venkanna; Gundla, Krishna Prasad; Addepally, Uma; Chimakurthy, Jithendra (European Journal of Chemistry, 2018)
A series of C-7 substituted-2-morpholino-N-(pyridin-2-ylmethyl)quinazolin-4-amine have been synthesized and biochemical assay was examined against α-glucosidase function inhibition activity. A structure activity and structure property relationship study was experimented to surface the new hit compound. This study led to the identification of C-7substituted quinazolines with minimum inhibitory concentrations (MICs) in the preffered micromolar range in addition with interesting physicochemical properties. Biological evaluation yielded eight analogs which rose with significant α-glucosidase inhibition potency (IC50 values < 2 μM, where reference compound (Acarbose) potency value is IC50 = 0.586 uM) and could be promising candidates for further lead optimization.